Sustainability Strategies and Women's Empowerment in Sidingkat Weaving: Economic, Social, and Environmental Impacts Analysis - Hasibuan, Masnilam; Pulungan, Ahmad Sayuti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to analyze the economic, social, and environmental impacts of the Sidingkat weaving business run by female artisans in Sidingkat Village, Padang Lawas Utara Regency. Additionally, this research formulates strategies that can support the sustainability of the weaving business and enhance the empowerment of women within the local community. The study employs a qualitative case study approach with data analysis following Miles et al.'s (2018) model through four stages: data collection, data reduction, data presentation, and conclusion drawing. Data were collected through in-depth interviews using structured questionnaires, direct field observations using observation checklists, and documentation review. The research involved 11 female weavers (100% of active weavers in the village), key stakeholders including local government officials and weaving entrepreneurs, and 30 customers of woven products. The findings show that 81.8% of weavers rely on the business as their primary income source, with 72.7% reporting increased income since joining. In terms of social impact, 100% of weavers experienced increased community recognition, and 81.8% reported greater social involvement. Regarding environmental practices, 63.6% of weavers have adopted eco-friendly materials, while 54.5% implement proper waste management. Customer satisfaction data reveals that 40% rate product quality as excellent, though only 33.3% consider the designs unique. Based on the analysis, several sustainability strategies are proposed, with 100% of weavers identifying access to capital as crucial, 81.8% emphasizing product innovation, and 63.6% highlighting the need for skills training. The study concludes that the Sidingkat weaving business has substantial growth potential if supported by appropriate policies and community backing, while contributing to women's empowerment and SME development in the traditional craft sector.